Alternative splicing alterations of Ca2+ handling genes are associated with Ca2+ signal dysregulation in myotonic dystrophy type 1 (DM1) and type 2 (DM2) myotubes. Issue 4 (June 2014) - Santoro, Massimo; Piacentini, Roberto; Masciullo, Marcella; Bianchi, Maria Laura Ester; Modoni, Anna; Podda, Maria Vittoria; Ricci, Enzo; Silvestri, Gabriella; Grassi, Claudio
<x xml:space="preserve">Abstract</x> Aims The pathogenesis of myotonic dystrophy type 1 (DM1) and type 2 (DM2) has been related to the aberrant splicing of several genes, including those encoding for ryanodine receptor 1 (RYR1), sarcoplasmatic/endoplasmatic Ca2+‐ATPase (SERCA) and α1S subunit of voltage‐gated Ca2+ channels (Cav1.1). The aim of this study is to determine whether alterations of these genes are associated with changes in the regulation of intracellular Ca2+ homeostasis and signalling. Methods We analysed the expression of RYR1, SERCA and Cav1.1 and the intracellular Ca2+ handling in cultured myotubes isolated from DM1, DM2 and control muscle biopsies by semiquantitative RT‐PCR and confocal Ca2+ imaging respectively. Results (i) The alternative splicing of RYR1, SERCA and Cav1.1 was more severely affected in DM1 than in DM2 myotubes; (ii) DM1 myotubes exhibited higher resting intracellular Ca2+ levels than DM2; (iii) the amplitude of intracellular Ca2+ transients induced by sustained membrane depolarization was higher in DM1 myotubes than in controls, whereas DM2 showed opposite behaviour; and (iv) in both DM myotubes, Ca2+ release from sarcoplasmic reticulum through RYR1 was lower than in controls. Conclusion The aberrant splicing of RYR1, SERCA1 and Cav1.1 may alter intracellular Ca2+ signalling in DM1 and DM2 myotubes. The differing dysregulation of intracellular Ca2+ handling in DM1 and DM2 may explain their distinct sarcolemmal hyperexcitabilities.